ILMU PENGETAHUAN DAN ETIKA: Pencarian Makna Dan Relevansi Dalam Narasi Qur’anik - Muhammad Adlan Nawawi; Abd. Muid N. (LP2M Universitas PTIQ Jakarta, 2022)
This study concludes that science needs ethical backing in the area of praxis. The development of science in the 20th century as a continuation of the passion of the Copernican revolution must refer to universal values, not just for the sake of science itself. So that in turn, science will benefit humanity. On the other hand, the real ethical foundation has been in the tradition from the beginning by the Qur'an through the holistic-universal messages it contains. In particular, the Qur'an asserts itself as a guide to life, a giver of good news and a warning to mankind. This shows that the qur'anic narrative is a narrative of instructions on how to live a better life by making science an instrument of civilization